Extinction risk of Mesoamerican crop wild relatives - Goettsch, Bárbara (2021)
Crop wild relatives (CWR) are plant taxa closely related to crops and are a source of high genetic diversity that can help adapt crops to the impacts of global change, particularly to meet increasing consumer demand in the face of the climate crisis. CWR provide vital ecosystem services and are increasingly important for food and nutrition security and sustainable and resilient agriculture. They therefore are of major biological, social, cultural and economic importance. Assessing the extinction risk of CWR is essential to prioritise in situ and ex situ conservation strategies in Mesoamerica to guarantee the long-term survival and availability of these resources for present and future generations worldwide. Summary: Ensuring food security is one of the world's most critical issues as agricultural systems are already being impacted by global change. Crop wild relatives (CWR)—wild plants related to crops—possess genetic variability that can help adapt agriculture to a changing environment and sustainably increase crop yields to meet the food security challenge. Here we report the results of an extinction risk assessment of 224 wild relatives of some of the world's most important crops (i.e. chilli pepper, maize, common bean, avocado, cotton, potato, squash, vanilla and husk tomato) in Mesoamerica—an area of global significance as a centre of crop origin, domestication and of high CWR diversity. We show that 35% of the selected CWR taxa are threatened with extinction according to The International Union for Conservation of Nature (IUCN) Red List demonstrates that these valuable genetic resources are under high anthropogenic threat. The dominant threat processes are land use change for agriculture and farming, invasive and other problematic species (e.g. pests, genetically modified organisms) and use of biological resources, including overcollection and logging. The most significant drivers of extinction relate to smallholder agriculture—given its high incidence and ongoing shifts from traditional agriculture to modern practices (e.g. use of herbicides)—smallholder ranching and housing and urban development and introduced genetic material. There is an urgent need to increase knowledge and research around different aspects of CWR. Policies that support in situ and ex situ conservation of CWR and promote sustainable agriculture are pivotal to secure these resources for the benefit of current and future generations.